Indeterminacy of International Law? - Severin, Meier (sui generis Verlag, 2021)
The most important (in)determinacy theses in international law since the 1920s are scrutinised in this book. As Severin Meier demonstrates, the extent of legal determinacy depends neither on some linguistic essence found in the text nor on theories that allegedly stand above practice. Instead, the (in)determinacy of law is shown to arise purely from practice. This reconceptualisation of a key discussion in legal philosophy provides a new perspective on the frame of meaning of legal norms.